Pengaruh Variasi Komposisi Terhadap Karakteristik Briket Campuran Sekam Padi Dan Kulit Jambu Mete - Aljaninansya, Rusdi; Mangalla, Lukas Kano; Sudia, Budiman (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2019)
This research aims to determine the characteristic briquettes of rice husk and sawdust. The treatment of this research includes non-carbonization processes, composition variation 30 % rice husk, 70 % sawdust powder, 50 % rice husk, 50 % sawdust powder, and 70 % paddy Husk, 30 % sawn wood powder (adhesive material considered homogeneous) as well as pressure variations (50 kgf/cm2, 100 kgf/cm2 and 150 kgf/cm2). The results of these things show that the higher the percentage of rice husk then the combustion time will be relatively longer, composition 50% rice husk and 50 % sawdust powder produces a higher maximum temperature than other composition, the higher the pressure given then the briquette density level will be greater and the resistance level the briquette will be higher and the Resistance index briquette is strongly influenced by the pressure and material composition briquette. Keywords: Briquet, rice husk, sawdust, non-carbonization